Population characteristics of benthopelagic Gymnoscopelus nicholsi (Pisces: Myctophidae) on the continental shelf of South Georgia (Southern Ocean) during austral summer - Ryan A. Saunders; Philip R. Hollyman; Sally E. Thorpe; Martin A. Collins (Polar Biology, 2022)
Southern Ocean myctophid fish (Family Myctophidae) are an important conduit of energy through foodwebs and between the surface layers and mesopelagic depths. Species that reside in both pelagic and near-bottom environments of continental shelves, such as Gymnoscopelus nicholsi and Gymnoscopelus bolini , may also be important in benthopelagic coupling, although their ecology and role in such processes remain unresolved. Here, we examined inter-annual variation in the depth of occurrence, biomass and population dynamics of benthopelagic G. nicholsi on the South Georgia shelf (100–350 m) using bottom trawl data collected between 1987 and 2019. Gymnoscopelus nicholsi was a regular component of the local benthopelagic community, particularly northwest of South Georgia, but was patchily distributed. It appeared to enter a benthopelagic phase at ~ 3 years, with annual growth and recruitment of year classes between ~ 3 and 5 years. However, transition of cohorts into the benthopelagic zone was not annual. There was clear inter-annual variation in G. nicholsi biomass and depth of occurrence. Shallower depth of occurrence was significantly ( P < 0.05) correlated with years of warmer summer sea surface temperatures, suggesting that inter-annual variation in local environmental conditions has an important influence on its migration behaviour and ecology. Our data also suggest that Antarctic krill is an important dietary component of the older G. nicholsi cohorts (~ 5 years) in the benthopelagic zone. We note that Gymnoscopelus bolini is rare in bottom trawl catches between 100 and 350 m, although Antarctic krill appears to dominate its diet from the available data. Our study provides important information on understudied myctophid species in a poorly investigated region of the water column that is relevant for Southern Ocean ecosystem studies, particularly in relation to understanding trophic connectivity between the pelagic and near-bottom realms.